1990
DOI: 10.1055/s-2007-1014538
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Strategies in the Search for Cognition Enhancers

Abstract: Memory is a complex multi-event procedure which is profoundly influenced by the overall psychological state. It is thus evident that there cannot be a "memory transmitter" and that many neurotransmitter systems are implicated in different parts of the cognitive process. In general, memory effects resulting from manipulation of the catecholamine systems are a reflection of altered arousal. Modification of cholinergic transmission or that of certain neuropeptides such as vasopressin would appear, however, to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When examining the effects on spatial memory, it was apparent that low doses of caffeine enhance performance while high doses deteriorate it. In fact, studies have concluded that activation of adenosine A 1 receptors strongly inhibits the release of acetylcholine from pyramidal hippocampal neurons [ 39 , 40 , 41 ]. Acetylcholine has been known to be important for memory storage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…When examining the effects on spatial memory, it was apparent that low doses of caffeine enhance performance while high doses deteriorate it. In fact, studies have concluded that activation of adenosine A 1 receptors strongly inhibits the release of acetylcholine from pyramidal hippocampal neurons [ 39 , 40 , 41 ]. Acetylcholine has been known to be important for memory storage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine A 1 receptors are expressed densely in the cerebral cortex and hippocampus (27,28). Activation of adenosine A 1 receptors strongly inhibits the release of acetylcholine from pyramidal hippocampal neurons (29)(30)(31). Acetylcholine has been shown to be important for memory storage (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, stimulation of the dorsal raphe and central injection of 5-HT impaired learning and memory (see Altman and Normile 1988;Briley 1990), whereas elevated synaptic 5-HT with reuptake inhibitors enhanced memory (Flood and Cherkin 1987;Altman and Normile 1988). In contrast, Jaffard et al (1991) reported memory impairments to 5-HT reuptake inhibitors.…”
Section: Introductionmentioning
confidence: 99%